2011
DOI: 10.1007/s00520-011-1290-x
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, randomized study of genetically modified recombinant human interleukin-11 to prevent chemotherapy-induced thrombocytopenia in cancer patients receiving chemotherapy

Abstract: This study shows that mIL-11 is well tolerated and has thrombopoietic activity equivalent to one third of the clinical dose of rhIL-11, indicating the potential of mIL-11 for use in the treatment of CIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Furthermore, the role of IL-11 in bone marrow failure syndromes, such as aplastic anemia and myelodysplastic syndrome, is being investigated in clinical trials [76,77]. On the other hand, to reduce the side effects and increase the activity of IL-11, a modified form of this cytokine, called IL-11 mutein was developed, which showed a promising profile with an increased potency and better safety in recent phase I and II clinical trials [78].…”
Section: Hematopoietic Activitiesmentioning
confidence: 99%
“…Furthermore, the role of IL-11 in bone marrow failure syndromes, such as aplastic anemia and myelodysplastic syndrome, is being investigated in clinical trials [76,77]. On the other hand, to reduce the side effects and increase the activity of IL-11, a modified form of this cytokine, called IL-11 mutein was developed, which showed a promising profile with an increased potency and better safety in recent phase I and II clinical trials [78].…”
Section: Hematopoietic Activitiesmentioning
confidence: 99%
“…[13][14][15] Up to date, the most effective approaches for treating the life-threatening complications of thrombocytopenia are platelet transfusion and supplementation with cytokines or thrombopoietic agents. [16][17][18][19] Nonetheless, their use is limited by side effects, costs and availability of blood donors. Therefore, more efficacious treatments to raise platelet count are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, chemotherapy-induced thrombocytopenia (CIT) is the most important cause of thrombocytopenia in patients with cancer [4]. Severe CIT not only has a risk of lifethreatening hemorrhagic complications but also may necessitate dose reduction and/or delay in chemotherapy schedules [3,[5][6][7][8]. Previous studies have indicated that various factors, such as platinum-based regimen, multiple high-risk chemotherapy treatments, multiple primary tumors, patients with lung cancer, and baseline thrombocyte count, have a high predictive value for CIT (3).…”
Section: Introductionmentioning
confidence: 99%
“…The demographic, clinical, laboratory, and pathological characteristics of Group 1 with CIT (n = 51, 40 %) and Group 2 without CIT (n = 80, 60 %) are displayed in Table 1. A total of 1,490 chemotherapy cycles were administered (median 10.6 cycles, range [6][7][8][9][10][11][12]. The median interval between cycles was 18 days (range 13-28).…”
Section: Introductionmentioning
confidence: 99%